2019
DOI: 10.1369/0022155419859870
|View full text |Cite
|
Sign up to set email alerts
|

Immunocytochemical Labeling of Rhabdomeric Proteins in Drosophila Photoreceptor Cells Is Compromised by a Light-dependent Technical Artifact

Abstract: Drosophila photoreceptor cells are employed as a model system for studying membrane protein transport. Phototransduction proteins like rhodopsin and the light-activated TRPL ion channel are transported within the photoreceptor cell, and they change their subcellular distribution in a light-dependent way. Investigating the transport mechanisms for rhodopsin and ion channels requires accurate histochemical methods for protein localization. By using immunocytochemistry the light-triggered translocation of TRPL ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 62 publications
0
10
0
Order By: Relevance
“…We therefore examined both Rhodopsin 1 (Rh1) and Myosin V (MyoV) expression in wild type and PIP82 mutant photoreceptors. In light exposed wild type photoreceptors Rh1 and MyoV immunofluorescence is only detected at the base of the rhabdomere and on vesicles in the vicinity of the rhabdomere terminal web [46,47]. We found that PIP82 does not colocalize with Rh1 and MyoV on vesicles but does colocalize with Rh1 localization at the base of the rhabdomere, the presumptive rhabdomere terminal web, (S7 Fig) in our fixation conditions [47].…”
Section: Plos Geneticsmentioning
confidence: 58%
See 1 more Smart Citation
“…We therefore examined both Rhodopsin 1 (Rh1) and Myosin V (MyoV) expression in wild type and PIP82 mutant photoreceptors. In light exposed wild type photoreceptors Rh1 and MyoV immunofluorescence is only detected at the base of the rhabdomere and on vesicles in the vicinity of the rhabdomere terminal web [46,47]. We found that PIP82 does not colocalize with Rh1 and MyoV on vesicles but does colocalize with Rh1 localization at the base of the rhabdomere, the presumptive rhabdomere terminal web, (S7 Fig) in our fixation conditions [47].…”
Section: Plos Geneticsmentioning
confidence: 58%
“…In light exposed wild type photoreceptors Rh1 and MyoV immunofluorescence is only detected at the base of the rhabdomere and on vesicles in the vicinity of the rhabdomere terminal web [46,47]. We found that PIP82 does not colocalize with Rh1 and MyoV on vesicles but does colocalize with Rh1 localization at the base of the rhabdomere, the presumptive rhabdomere terminal web, (S7 Fig) in our fixation conditions [47]. In newly eclosed PIP82 mutant photoreceptors, Rh1 and to a much lesser extent MyoV were no longer constrained to vesicles and the rhabdomere terminal web but accumulated improperly on the basal lateral membranes (Fig 7), despite overall seemingly normal levels of Rh1 (Fig 6C).…”
Section: Plos Geneticsmentioning
confidence: 99%
“…As reported previously, Rh1 either fills the entire rhabdomere, forms a crescent-shaped pattern, or is restricted to the base or the lateral edges of the rhabdomere ( Chen et al, 2017 ; Chinchore et al, 2009 ; Mitra et al, 2011 ; Orem et al, 2006 ; Wang et al, 2014 ; Xiong et al, 2012 ). Differences in localisation have been attributed to inconsistencies in antibody penetration due to either the dense packing of microvilli in the rhabdomeres ( Xiong et al, 2012 ) or to a light-induced staining artefact ( Schopf et al, 2019 ). Rh1 staining is observed in rhabdomeres (red arrowheads in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Consistent with previous reports, Rh1 immunostaining does not fill the entire rhabdomere. This has been attributed to the inaccessibility of the antibody inside the tightly packed microvilli and light activation of phototransduction ( Schopf et al, 2019 ). Rh1 staining is substantially reduced in rhabdomeres of mutant PRCs ( ninaE 7 , C).…”
Section: Resultsmentioning
confidence: 99%
“…Increased hydroxylation of sphingolipids was observed to be one of the major lipidomic changes during the polarization of MDCK cells (Sampaio et al, 2011), and inhibition of sphingolipid Consistent with previous reports, Rh1 immunostaining does not fill the entire rhabdomere. This has been attributed to the inaccessibility of the antibody inside the tightly packed microvilli and light activation of phototransduction (Schopf et al, 2019). Rh1 staining is substantially reduced in rhabdomeres of mutant PRCs (ninaE 7 , C).…”
Section: Discussionmentioning
confidence: 99%